Phytosociological analysis of alpine swards and heathlands (pioneer patches) on ridges and peaks in the Julian Alps (NW Slovenia) - Dakskobler, Igor; Surina, Boštjan (Hacquetia, 2016)
We conducted a phytosociological analysis of more than 250 relevés in the Julian Alps and compared them with similar communities elsewhere in the Alps and in the Dinaric Alps to describe the following new syntaxa of alpine swards and heathlands from the alliance Caricion firmae (class Elyno-Seslerietea): Saxifrago squarrosae-Caricetum mucronatae, Saussureo pygmaeae-Caricetum rupestris, Seslerio sphaerocephalae-Dryadetum octopetalae, Homogyno discoloris-Vaccinietum gaultherioidis, Saxifrago paniculatae-Caricetum fuliginosae and Homogyno discoloris-Loiseleurietum caricetosum firmae, the new association Achilleo clavennae-Elynetum myosuroidis from the alliance Oxytropido-Elynion and two new syntaxa from the alliance Loiseleurio-Vaccinion (class Loiseleurio-Vaccinietea): Homogyno alpinae-Vaccinietum gaultherioidis and Empetro-Vaccinietum gaultherioidis rhododendretosum hirsuti. Many species that are rare, of conservation concern or protected in Slovenia occur in the newly described communities.